LA EDAD COMO FACTOR DEL COMPORTAMIENTO DEL CONSUMIDOR DE PRODUCTOS ORGÁNICOS - Armando Medina Jiménez; Milka Elena Escalera; Miguel Ángel Vega Campos (European Scientific Journal, ESJ, 2014)
Organic products have gained great popularity for two main reasons. Firstly, the consumer perceives it as healthy foods free of pesticides and fertilizers. Secondly, to contribute to the environment. The main objective of this paper is to analyze whether age influences the consumer behavior when purchasing organic products. This research is quantitative, causal, not experimental and transversal. The study sample was 245 consumers in supermarkets in the capital of San Luis Potosí offering these products. The data analysis was performed using the AMOS program to predict one variable observed (age) as a linear combination of five other observed variables (separation of materials, shopping for health reasons, love for nature, learn about nature, outrage at the unnecessary consumption of natural resources, environmental damage). The results give evidence that age influences consumer behavior when purchasing organic products. Buying organic products increases with age; older consumers look to buy organic products for the health benefits.